Historical sources of professional education at the State School Professor Anísio Teixeira (1985-2002) (Research, Society and Development, 2020)
This article is a historical and documentary research that has been developed in the Graduate Program in Professional Education (PPGEP), of the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), in the history line , historiography and memory of professional education, at E. E. Prof. Anísio Teixeira (1985-2002), in Natal-RN. The purpose of this writing is to reflect on what the institution's historical sources say in the time already announced. The search for these sources has been carried out in the school's archives, with documents such as: individual records, diplomas, school transcripts, minutes, point books, legislation and photographs. Documentary research in progress in which the value of documents and archives is perceived is extremely important for the reconstruction of the history of professional education in this researched institution and more than that for the history of education in RN.